Novel visual perceptual phenomenon in isoluminant bi-coloured square-wave gratings - Tan, Azaac Wei En (2019)
Visual illusions, beyond their ability to entertain, reveal the “flaws” and limits of human perception, and how our visual senses can be fooled. In this study, we present a novel illusory percept generated by isoluminant bi-coloured square-wave gratings. We document the physical characteristics of the stimuli that affect the strength of the illusion and the illusory colours perceived, and consider potential mechanisms underlying this phenomenon. In line with our hypotheses, the results reveal that the strength of the illusion varies with the spatial frequency of the grating, and that the illusory percept is motion-dependent. Analysis of the illusory colours perceived reveals a relationship between the stimulus colours and the illusory colours perceived. This relationship demonstrates integration of the typically independent red-green parvocellular and blue-yellow koniocellular channels in the visual pathway. Overall, this pioneering study points towards a new mechanism of colour perception and integration, possibly in the early visual cortex. Possible future directions of research employing these coloured square-wave gratings are discussed.